2012
DOI: 10.1016/j.neuroimage.2011.09.083
|View full text |Cite
|
Sign up to set email alerts
|

Neural representations involved in observed, imagined, and imitated actions are dissociable and hierarchically organized

Abstract: The fact that action observation, motor imagery and execution are associated with partially overlapping increases in parieto-frontal areas has been interpreted as evidence for reliance of these behaviors on a common system of motor representations. However, studies that include all three conditions within a single paradigm are rare, and consequently, there is a dearth of knowledge concerning the distinct mechanisms involved in these functions. Here we report key differences in neural representations subserving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
127
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(146 citation statements)
references
References 70 publications
19
127
0
Order By: Relevance
“…Similar findings of neural reactivation of sensory and motor brain areas have been found in other cognitive abilities, for example, spatial working memory (Awh & Jonides, 2001), motor imagery (Munzert, Lorey, & Zentgraf, 2009;Macuga & Frey, 2012), and language (Hauk, Johnsrude, & PulvermĂĽller, 2004). In conclusion, there is a general trend of reactivating brain areas for perception and action in other cognitive functions.…”
Section: Episodic Memory: Neural Overlapsupporting
confidence: 76%
See 2 more Smart Citations
“…Similar findings of neural reactivation of sensory and motor brain areas have been found in other cognitive abilities, for example, spatial working memory (Awh & Jonides, 2001), motor imagery (Munzert, Lorey, & Zentgraf, 2009;Macuga & Frey, 2012), and language (Hauk, Johnsrude, & PulvermĂĽller, 2004). In conclusion, there is a general trend of reactivating brain areas for perception and action in other cognitive functions.…”
Section: Episodic Memory: Neural Overlapsupporting
confidence: 76%
“…At other times, reactivations are triggered automatically by the aspects of the environment, such as when reading action words (Hauk, Johnsrude, & PulvermĂĽller, 2004). Macuga and Frey (2012) compared three different conditions that differed among other things on their reliance on input from the environment and the body: observation, imagery, and imitation of simple finger movements. Consistent with the reactivation hypothesis they found that …all three conditions were associated with increased bilateral increases in activity within a common set of frontal (premotor, pre-SMA), posterior parietal, superior temporal and primary sensorimotor areas, as well as subcortical (thalamus, putamen) regions traditionally implicated in visually-guided bimanual behavior.…”
Section: Internally or Externally Cued Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that compared observation, imagery, and execution have included the measurement of the reaching movements of arms using fMRI [8], the reaching motion of the arm using virtual reality and fNIRS [46], wrist movements using fMRI [47], hand movements using transcranial magnetic stimulation (TMS) [48,49], finger movements using fMRI [7], ankle movements using fMRI [50], and the squatting movements of the lower limbs using the heart and breathing rates as indicators [51]. Each of these studies reported similar results under all three conditions.…”
Section: Comparison Of Movement Modesmentioning
confidence: 99%
“…However, the majority of this literature investigated only one mode of covert movement mode or, at most, compared two modes, usually motor imagery and observation (Clark et al, 2003;Filimon et al, 2007;Iseki et al, 2008;Lui et al, 2008;Macuga and Frey, 2012;Munzert et al, 2008;Piefke et al, 2009;Roosink and Zijdewind, 2010;Wang et al, 2008). Therefore inferences between studies have to be made when comparison between all modes of covert movement is to be conducted.…”
Section: Introductionmentioning
confidence: 99%